A 5-bp mutation within MSTN/GDF8 gene was significantly associated with growth traits in Inner Mongolia White Cashmere goats. Issue 5 (1st October 2021) - Bi, Yi; He, Libang; Feng, Bo; Lan, Xianyong; Song, Xiaoyue; Qu, Lei; Pan, Chuanying
Abstract: Myostatin ( MSTN ) gene, also known as growth and differentiation factor 8 ( GDF8 ) gene, is a negative regulator of skeletal muscle growth and development, especially the number, size and type of muscle fibers. Its mutations contribute to the double-muscling (DBM) phenomenon which significantly increases the muscle mass. Hence, variations within MSTN / GDF8 gene receive so much attention in several kinds of species such as bovines, poultries, goats, sheep, horses. A 5-base pairs (bp) indel in the 5' untranslated region (5'UTR) of goat MSTN / GDF8 was verified to be significantly associated with growth traits except Inner Mongolia White Cashmere (IMWC) goats. Given that almost all sample sizes were below 150, we enlarged sample sizes to more than 500 to uncover the association between the 5-bp indel and growth traits in IMWC goats. Only two genotypes (deletion/deletion (DD) and insertion/deletion (ID)) were found, and DD genotypes were dominant genotypes. The detected locus displayed low genetic diversity (PIC = 0.090). Interestingly, the association analyses revealed that the 5-bp indel had a significant effect on the chest depth ( p = 0.003), and DD genotypes were dominant genotypes. Hinted that the 5-bp indel could act as an effective marker in molecular marker-assisted selection (MAS) processes for selection of excellent goat individuals.